The Effect of Temperature on Tensile Strength of Polypropylene Plate Material Using Hot Gas Welding (HGW) Method - Rohman Rohman; Anjar Prasetyo; Amri Abdulah; Karyadi Karyadi; Thiyana Thiyana; Sukarman Sukarman (Jurnal Teknik Mesin Mechanical Xplore, 2022)
This study focuses on plastic welding, a technique that employs polypropylene plastic material in 3600-litre reservoir applications. The liquid pressure within it causes hydrostatic pressure in the reservoir. The pressure in the reservoir is approximately 0.01 N/mm2. This study aimed to determine how frequently polypropylene joints leak or sustain damage as a result of welding. Hot gas welding (HGW) with a v-groove connection type is employed (v-grove). Specimens of polypropylene were prepared in accordance with ASTM D638-I. In this study, the input parameters were chosen by varying the welding position and the machine's setting temperature. The results indicated that the required welding temperature for 5 mm-thick polypropylene plastic ranged between 220 and 280 degrees Celsius. In the tensile test on samples S1, S2, and S3, the average decrease in tensile strength of the three test objects was 13.84 N/mm2, 15.98 N/mm2, and 15.21 N/mm2, respectively